1997
DOI: 10.1177/001698629704100103
|View full text |Cite
|
Sign up to set email alerts
|

Specialized Counseling Services for Gifted Youth and Their Families: A Needs Assessment

Abstract: Although many authors have recommended counseling for the gifted (Colangelo, 1991;Kerr, 1986;

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
14

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 58 publications
2
33
0
14
Order By: Relevance
“…Morelock, 1992. Η ζεσξία ηνπ Renzulli(2005) Σπγθεθξηκέλα, έξεπλεο έρνπλ αλαγλσξίζεη σο βαζηθά ραξαθηεξηζηηθά ζηα ραξηζκαηηθά παηδηά, ηελ απνθιίλνπζα λφεζε (δεκηνπξγηθφηεηα), ηε δηέγεξζε, ηελ επαηζζεζία, ηελ νμπκέλε αληίιεςε, ηελ ηειεηνκαλία (Feldhusen, 2005. Moon, Kelly & Feldhusen, 1997.…”
Section: χαριζμαηικόηεηαunclassified
“…Morelock, 1992. Η ζεσξία ηνπ Renzulli(2005) Σπγθεθξηκέλα, έξεπλεο έρνπλ αλαγλσξίζεη σο βαζηθά ραξαθηεξηζηηθά ζηα ραξηζκαηηθά παηδηά, ηελ απνθιίλνπζα λφεζε (δεκηνπξγηθφηεηα), ηε δηέγεξζε, ηελ επαηζζεζία, ηελ νμπκέλε αληίιεςε, ηελ ηειεηνκαλία (Feldhusen, 2005. Moon, Kelly & Feldhusen, 1997.…”
Section: χαριζμαηικόηεηαunclassified
“…Mereka juga mempunyai isu-isu psikologikal yang unik seperti isu perkembangan emosi yang tidak selari dengan usia mereka, isu perfectionism, dan isu tingkah laku anti-sosial (Noriah & Abu Yazid 2010a). Walaupun perkhidmatan kaunseling tidak boleh dinafikan sebagai satu sistem sokongan penting bagi sesuatu program pendidikan pintar dan berbakat (VanTassel-Baska 2013, namun, hakikatnya, kajian-kajian ilmiah yang berpaksi kepada pelaksanaan perkhidmatan ini untuk populasi pelajar pintar dan berbakat amat terbatas serta jarang sekali dilakukan (Moon et al 1997;Shore et al 1991;Kerr 1991;Myers & Pace 1986). Natijahnya, populasi pelajar pintar dan berbakat memerlukan bentuk perkhidmatan kaunseling yang berbeza dan khusus disebabkan keunikan personaliti dan isu-isu yang lazim dihadapi mereka (Morawska & Sanders 2009;Peterson 2006;Ryan 2001Ryan , 1999Sajjadi 2000;Zaffrann & Colangelo 1977).…”
Section: Pengenalanunclassified
“…KESIMPULAN Kesimpulannya, dapatan kajian ini menunjukkan bahawa pola isu yang dihadapi oleh pelajar pintar dan berbakat dalam persekitaran pendidikan merangkumi empat domain utama iaitu: (1) kerjaya, (2) akademik, (3) sosial, dan (4) psiko-emosi. Secara umum, klasifikasi isu yang dinyatakan ini sejajar dengan pelbagai dapatan kajian pendidikan pintar dan berbakat yang telah dilakukan dalam konteks yang serupa (VanTassel-Baska 1990;Rimm 2003, Colangelo 2003Bee 1999;Moon et al 1997). Oleh kerana domain isu kerjaya dan akademik merupakan dua domain yang utama, maka keperluan perkhidmatan kaunseling untuk populasi pelajar ini harus dijuruskan kepada bentuk perkhidmatan kaunseling kerjaya dan bimbingan akademik.…”
Section: Dapatan Dan Perbincangan Kepelbagaian Isu Pelajar Pintarunclassified
“…Gifted children may behave similarly to either their chronological age or mental age peers in specific domains yet entirely differently to either in others (Lehman & Erdwins, 2004). In light of this inconclusiveness, it is difficult to determine whether gifted children are hindered or helped by their giftedness, and indeed individual differences are likely to be experienced by individual children.However, it can be concluded that gifted children as a group may experience unique social-emotional challenges related to their giftedness which could thwart their optimal development and require support from their parents and teachers in coping with stressors.Despite research that highlights the needs of gifted children, Australian empirical research has focused mainly on the cognitive needs of gifted primary school children and differentiation of the curriculum, as has the majority of international research (Cross, 2011;Kennedy, 1995;Lamont, 2012;Moon, Kelly, & Feldhusen, 1997;Tieso, 2007). However, as humans, we are both thinking and feeling beings; empirical research is therefore needed to explore the social-emotional needs of gifted primary school-aged children.…”
mentioning
confidence: 99%
“…Despite research that highlights the needs of gifted children, Australian empirical research has focused mainly on the cognitive needs of gifted primary school children and differentiation of the curriculum, as has the majority of international research (Cross, 2011;Kennedy, 1995;Lamont, 2012;Moon, Kelly, & Feldhusen, 1997;Tieso, 2007). However, as humans, we are both thinking and feeling beings; empirical research is therefore needed to explore the social-emotional needs of gifted primary school-aged children.…”
mentioning
confidence: 99%